Self-Differentiation as a Mediator of the Effects of Parenting Styles and Self-Efficacy on Parasuicidal Behavior in Adolescents - Castillo, Sheryll Ann; Sivako, Kefilwe (12th International Scholars Conference 2025, 2026)
Parasuicidal behaviors—intentional self-harm without the intent to die—are an increasingly prevalent concern in adolescent mental health, linked to complex intrapersonal and environmental factors. This study explored the mediating role of self-differentiation in the relationships between self- efficacy, parenting styles, and parasuicidal behavior among adolescents. A total of324 adolescents from Botswana participated in the study using standardized instruments, including the Parenting Styles and Dimensions Questionnaire (PSDQ), Differentiation of Self Inventory (DSI), and Deliberate Self-Harm Inventory (DSHI).Structural equation modeling (SEM) revealed a fully mediated model. Authoritarian maternal parenting predicted lower self-differentiation (β = –0.182, p < .001), increasing parasuicidal behavior (β = –0.253, p < .001), while authoritative paternalparenting and self-efficacy both predicted higher self-differentiation (β = 0.193, p = .001; β = 0.277, p < .001), which in turnreduced parasuicidal behavior. Model fit indices (CFI = 0.96, TLI = 0.95, RMSEA = 0.045) affirmed the robustness of this pathway. These findings emphasize self-differentiation as a psychological buffer against self-harming tendencies and underscore the protective roles of supportive parenting and self-efficacy. Implications include integrating emotional autonomy and self-efficacy development into school counseling programs. Recommendations for culturally grounded interventions are discussed.